KADOKU: Digital Innovation in Finding the Best Gifts Through Web Platform - Purwanto, Heri; Kamaulid, Tabiya Rayna; Andriansyah, Edi; Anggraeni, Octa Putri; Manaf, Khaerul (@is The Best : Accounting Information Systems and Information Technology Business Enterprise, 2024)
Gift exchange is a significant social phenomenon, serving as a form of communication and emotional expression. However, the challenges of modern life often make it difficult for individuals to select and acquire suitable gifts within a limited timeframe. This research addresses the issue by designing and developing a Gift Sales Website named Kadoku, which integrates the concept of E-Commerce to support gift outlet business owners. Utilizing the Scrum methodology, the website incorporates a live help feature to assist users in finding their desired gifts efficiently. The system underwent black box testing to ensure functional validity, and its usability was evaluated through a survey of 15 respondents. The findings revealed that 85% of users considered the website easy to operate, 84% stated it facilitated their gift selection process, and 83% expressed overall satisfaction with the platform as a solution for simplifying gift searches. By averaging the user feedback scores, the website achieved an overall agreement level of 77.02%, demonstrating its effectiveness in addressing user needs. This study highlights the potential of E-Commerce platforms, developed with agile methodologies like Scrum, to enhance user experience and provide practical solutions for everyday challenges. Kadoku serves as a viable model for future innovations in the gift retail sector.